O trabalho em equipes autogerenciadas e sua influência na motivação dos empregados - Bianco, Alessandra (2003)
Over the last years many authors have been supporting that some factors such as autonomy and human interaction are related with higher levels of motivation in labor. They also regard self-managed working groups as capable of merging both factors, given that autonomy becomes an issue as the self-management is encouraged and interaction is a direct consequence of the relationship among different people. The objective of this research is to offer some contribution to the existing theory, investigating the means by which the work in self-managed groups affects the motivation of the employees. In order to assemble meaningful portion of the existing knowledge about the theme, a bibliographic research was carried out in the first stage of this study. To get in touch with the practice a field research was performed in the second stage, by gathering the opinion of a number of professionals in different activity areas. From the fileld research findings. and founded on the bibliographic data. it was observed that the work within self-managed groups not only positively influences the motivation of the employees that have gone through that. but also generates good expectation on those that have not had such opportunity thus far. The major reasons for that positive influence were found to be the enhancement of the workers role in the decision-taking process and the encouragement of their creativity.